Short-Term Water- and Land-Based Exercise Training Comparably Improve Exercise Capacity and Vascular Function in Patients After a Recent Coronary Event: A Pilot Randomized Controlled Trial - Vasić, Danijela; Novaković, Marko; Božič Mijovski, Mojca; Barbič Žagar, Breda; Jug, Borut (Frontiers in Physiology, 2019)
Background We hypothesized that a 2-week twice daily aquatic endurance plus calisthenics exercise training program: (i) increases aerobic exercise capacity (peak oxygen uptake/V˙O2peak), (ii) improves endothelium-dependent flow-mediated vasodilation (FMD), and (iii) reduces circulating markers of low-grade inflammation and hemostasis, as compared to land-based endurance plus calisthenics exercise training or no exercise in patients undergoing short-term residential cardiac rehabilitation after a recent coronary artery disease (CAD) event. Methods Patients with a recent myocardial infarction or revascularization procedure were randomized into two interventional groups and a control group. The interventional groups underwent supervised aerobic endurance plus calisthenics exercise training either in thermo-neutral water or on land at moderate intensity (60–80% of the peak heart rate achieved during symptom-limited graded exercise testing) for 30 min twice daily for 2 weeks (i.e., 24 sessions). The control group was deferred from supervised exercise training for the 2-week duration of the intervention, but was advised low-to-moderate intensity physical activity at home while waiting. At baseline and after the intervention period, all participants underwent estimation of aerobic exercise capacity, brachial artery flow-mediated dilatation (FMD, measured ultrasonographically at rest and during reactive hyperemia after 4.5 min of forearm cuff inflation), markers of cardiac dysfunction (NT-proBNP), inflammation (hsCRP, IL-6, IL-8, IL-10), cell adhesion (ICAM, P-selectin), and hemostasis (fibrinogen, D-dimer). Results A total of 89 patients (mean age 59.9 ± 8.2 years, 77.5% males, V˙O2peak at baseline 14.8 ± 3.5 ml kg-1 min-1) completed the study. Both exercise modalities were safe (no significant adverse events recorded) and associated with a significant improvement in V˙O2peak as compared to controls: age and baseline V˙O2peak-adjusted end-of-study V˙O2peak increased to 16.7 (95% CI 16.0–17.4) ml kg-1 min-1 with land-based training (p < 0.001 for change from baseline) and to 18.6 (95% CI 17.9–19.3) ml kg-1 min-1 with water-based training (p < 0.001 for change from baseline), but not in controls (14.9 ml kg-1 min-1; 95% CI 14.2–15.6; p = 0.775 for change from baseline). FMD also increased in both intervention groups (from 5.5 to 8.8%, p < 0.001 with land-based, and from 7.2 to 9.2%, p < 0.001 with water-based training, respectively), as compared to controls (p for change 0.629). No significant changes were detected in biomarkers of inflammation, cell adhesion or hemostasis, whereas levels of NT-proBNP (marker of cardiac dysfunction) decreased in the water-based training group (p = 0.07 vs. controls). Conclusion Endurance plus calisthenics exercise training in thermo-neutral water is safe, and improves aerobic exercise capacity and vascular function in patients undergoing short-term residential cardiac rehabilitation after a recent CAD event. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT02831829.